BLOCKCHAIN ADOPTION IN THAILAND’S ELECTIONS: PERSPECTIVES, LIMITATIONS, AND THE PROPOSED TBERM MODEL - Peeraphirom, Charm; Chanwimalueng, Waiwit (JWP (Jurnal Wacana Politik), 2026)
This study assesses Thailand’s readiness for blockchain-based elections by utilizing qualitative methods and semi-structured interviews with five experts in law, technology, economics, and administration. The data were analyzed through the dimensions of privacy, accessibility, transparency, security, and scalability. Findings reveal that while blockchain enhances integrity, significant barriers exist including insufficient transaction throughput, high costs, voter coercion risks, and limited digital literacy. Legal gaps regarding the PDPA also hinder adoption. Consequently, the study proposes the Thailand Blockchain Election Readiness Model (TBERM) which is a hybrid framework integrating blockchain auditing with physical polling units to mitigate security and accessibility concerns. The results indicate that Thailand is not yet prepared for full nationwide adoption but can transition through the proposed TBERM. The study recommends incremental implementation via pilot projects supported by legal reforms and public education.